MUSIC AS A MEANS OF SPIRITUAL EDUCATION OF YOUTH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article discusses issues such as the role and importance of music in schools, the musical creativity of Eastern scholars, and the importance of age characteristics in music education.